Pityriasis rosea-like rash after messenger RNA COVID-19 vaccination: A case report and review of the literatureCapsule Summary - Jordan E. Buckley, MD; Laura N. Landis, BA; Ronald P. Rapini, MD (Elsevier, 2022)
A spectrum of cutaneous reactions to SARs-CoV-2 (COVID-19) vaccines have been reported in the literature. We present a case of a pityriasis rosea-like rash occurring after Pfizer COVID-19 vaccination and review cases of pityriasis rosea (PR)/PR-like eruption (PR-LE) after mRNA COVID-19 vaccine published in the medical literature. Of the 30 cases found, none experienced severe adverse effects and the rash resolved in an average of 5.6 weeks. It is important for physicians to be aware of this self-limited reaction so they can reassure and appropriately counsel patients that it is safe to receive subsequent vaccine doses despite the cutaneous eruption. Additionally, differences in incidence of this reaction after Pfizer and Moderna vaccination may suggest a differing host immune response incited by these vaccines which warrants further investigation.